2000
DOI: 10.1103/physrevb.61.1311
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the magnetization reversal of an Fe thin film on Si(111)

Abstract: The magnetic behavior of a 60-Å Fe film grown on Si͑111͒ is reported and discussed. Scanning tunneling microcopy images showed Fe stripes along one of the ͗110͘ directions in the ͑111͒ plane, which favors easy magnetization axis parallel to the stripes. Inverted in-plane hysteresis loops and loops with unusual local peaks were measured and interpreted. A phenomenological model was proposed to interpret the magnetization data and an excellent concordance between the experimental and the calculated curves was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…NRM, also known as negative coercivity or inverted hysteresis loop, has been observed in heterogeneous thin films, and heterogeneous NP systems (with amorphous matrix, large particle size distribution or core shell structure) by various experimental techniques (e.g., Vibrating Sample Magnetometer, SQUID magnetometry, Alternating Gradient Force, Magneto-optical Kerr Effect and Hall probe imaging)123456789. In normal magnetic behavior the magnetization follows the applied field with a phase lag, whereas in magnetic systems that display NRM, the magnetization of the descending branch of the hysteresis loop becomes negative while the applied field is still positive.…”
mentioning
confidence: 99%
“…NRM, also known as negative coercivity or inverted hysteresis loop, has been observed in heterogeneous thin films, and heterogeneous NP systems (with amorphous matrix, large particle size distribution or core shell structure) by various experimental techniques (e.g., Vibrating Sample Magnetometer, SQUID magnetometry, Alternating Gradient Force, Magneto-optical Kerr Effect and Hall probe imaging)123456789. In normal magnetic behavior the magnetization follows the applied field with a phase lag, whereas in magnetic systems that display NRM, the magnetization of the descending branch of the hysteresis loop becomes negative while the applied field is still positive.…”
mentioning
confidence: 99%
“…In addition, the two smaller square loops along hysteresis are related to the present of step edges. Our study on the angular dependent coercivity [7] has shown that the superposition of fourfold and uniaxial anisotropy in present studied system is the same as in Co-Cu [4] and Fe-Si(111) [10], i.e., that an easy fourfold axis coincides with the easy twofold axis. We have carried out measurements of the magnetic reversal of the film by systematically increasing temperatures.…”
Section: Methodsmentioning
confidence: 77%
“…From XRD analysis, the Mo(001) plane tilts by an angle 2. 5 4 from the axis bcc [1]- [10]. With the known value of Mo in-plane lattice constant and the value of the tilt angle measured from XRD, the average terrace size and the step height is estimated to be around 3 nm and 0.187 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20][21][22] Such unusual loops are interpreted considering either magnetostatic or exchange interaction between layers with non-identical magnetic phases (i.e., both having uniaxial in plane anisotropy or even ferro/antiferro character). In the present case, inverted loops are a consequence of the strong local demagnetizing fields.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] To understand it, we should consider that the measured loop actually represents magnetization against applied magnetic field, where the presence of additional field component, particularly local demagnetizing fields, is not taken into account. In our present case of thick wires, the local inverted loops in the region, close but not at the very end of the microwires, denote the existence of a significant local redistribution of magnetic moments.…”
Section: Magneto-optical Kerr Effect Measurementsmentioning
confidence: 99%